Study of the pleitropic effects of sodium 2-((4-phenyl-5-thiophen3-ylmethyl)-1,2,4-triazol-3-yl)thio)ethanoate in conditions of experimental hyperlipidemia - Bilai, I. M.; Khilkovets, A. V.; Bilai, A. I.; Veretelnyk, O. V.; Білай, Іван Михайлович; Хільковець, Анастасія Валеріївна; Білай, Андрій Іванович; Веретельник, Олександр Володимирович (My University, 2025)
The aim of the study is to study the effect of sodium 2-((4-phenyl-5-(thiophene-3-ylmethyl)-1,2,4-triazole-3-yl)thio)ethanoate compound on pleiotropic biomarkers under experimental hyperlipidemia. Materials and methods. The study of the biological activity of sodium salt 2-((4-phenyl-5-(thiophene-3-ylmethyl)-1,2,4-triazole-3-yl)thio) ethanoic acid was conducted on 20 white nonlinear rats weighing 160–310 g, obtained from the nursery of the Institute of Pharmacology and toxicology of the National Academy of Medical Sciences of Ukraine. Experiments were performed on the basis of a certified vivarium and the Department of Clinical Pharmacy, Pharmacotherapy, Pharmacognosy and Pharmaceutical chemistry of Zaporizhia State Medical and Pharmaceutical University. The animals were kept under standard conditions in accordance with the requirements of EU directive 2010/63/ EC and order of the Ministry of Education and Science No. 249 of 01.03.2012. Experimental hyperlipidemia was modeled by administration of cholesterol and ergocalciferol for 5 days. Serum levels of eNOS (enzyme immunoassay), CRP, MV-CPK, and D-dimer (ACCENT-200 biochemical analyzer, corresponding reagents produced by Cloud-Clone, Cormay, and Vector-best) were determined. Метою дослідження є: вивчення дії сполуки натрій 2-((4-феніл-5-(тіофен-3-ілметил)-1,2,4-триазол-3-іл)тіо) етаноату на окремі плейотропні біомаркери, в умовах експериментальної гіперліпідемії. Матеріали та методи. Дослідження біологічної активності натрієвої солі 2-((4-феніл-5-(тіофен-3-ілметил)-1,2,4-триазол-3-іл)тіо)етанової кислоти проведено на 20 білих нелінійних щурах масою 160–310 г, отриманих з розплідника Інституту фармакології та токсикології АМН України. Експерименти виконували на базі атестованого віварію та кафедри клінічної фармації, фармакотерапії, фармакогнозії та фармацевтичної хімії; Запорізького державного медико-фармацевтичного університету. Тварини утримувалися в стандартних умовах, згідно з вимогами Директиви ЄС 2010/63/ЄС та наказу МОН № 249 від 01.03.2012. У сироватці крові визначали рівні eNOS (імуноферментний метод), СРБ, МВ-КФК і Д-дімеру (біохімічний аналізатор ACCENT-200, відповідні реагенти виробництва Cloud-Clone, Cormay, Вектор-Бест).
Дослідження плейотропних ефектів натрію 2-((4-феніл-5-тіофен-3-ілметил)-1,2,4-триазол-3-іл) тіо) етаноату в умовах експериментальної гіперліпідемії
Keywords: 1,2,4-triazoles; hyperlipidemia; pleiotropic effects; 1,2,4-тріазоли; гіперліпідемія; плейотропні ефекти